Beyond techno-utopia and its discontents: On the role of utopianism and speculative fiction in shaping alternatives to the smart city imaginary. (January 2020) - Bina, Olivia; Inch, Andy; Pereira, Lavínia
Highlights: Critique of smart city imaginaries (SCI) reproduces limitations in social scientific engagement with the future. Fiction can animate social science warnings about SCI to deepen critique and aid construction of alternative futures. Utopia can be mobilized as an heuristic method to "educate desire" for alternative futures. Results highlight need to humanize and renature 'techno-utopianism' of SCI. Analysis shows value of plural futures epistemologies to explore and reshape SCI. Abstract: In recent years, the ösmart city' has become established in policy and planning discourse, embedding visions of an urban future where ubiquitous technology offers efficient solutions to the pathologies of the contemporary city. In response, a rapidly growing social-scientific literature is critically exploring how the smart city imaginary (SCI) promotes ötechno-utopian' fantasies, ignoring the risks of a technologically determined future. In this paper we begin by considering SCI as emblematic of the colonization of contemporary (urban) futures by vested interests, arguing for the need for diverse and plural imaginaries and thus for a re-engagement of the social sciences. We explore how critical social scientific contributions to shaping futures might be deepened through further engagement with utopian theory and speculative fiction, two traditions of future-orientated thinking that seek to combine critique with constructive thinking about alternatives. We therefore contribute to ö50 + 50 Theme 2: Framing Futures in 2068-the limits of and opportunities for futures research' by 1) extending critique of contemporary claims about (smart urban) futures, and; 2) exploring how utopianism and fiction can expand ways of thinking, imagining and knowing futures.